Peningkatan Hasil Belajar PAK melalui Model PBL dengan Media Bermain Peran di Kelas IV - Atik Atik; Ansel Joko Prayitno (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
The study entitled "Improving PAK Learning Outcomes with the Problem-Based Learning (PBL) Model Assisted by Role Play Media for Phase B, Grade 4 Students of SDN 24 Sungai Uluk" was motivated by the low academic performance of students in the Catholic Religious Education and Character Education (PAKBP) subject. The aim of this research was to determine the extent to which the Problem-Based Learning (PBL) model can enhance students’ learning outcomes in PAK. This study is a Classroom Action Research (CAR) conducted in two learning cycles. Each cycle consists of four stages: planning, action, observation, and reflection. In the first cycle, the lecture method was used, while in the second cycle, the PBL model was implemented, focusing on solving real-life problems commonly encountered by students. The PBL implementation in the second cycle was supported by role play media to improve students' comprehension and engagement. The assessment results from the end of the second cycle indicated an improvement in students' learning outcomes, and observations revealed increased student participation in the learning process. These findings suggest that the use of the PBL model assisted by role play media can be an effective alternative to enhance both the learning outcomes and active involvement of Grade 4 students in the PAK subject at SDN 24 Sungai Uluk.